Birrul Walidain in the Perspective of Islamic Family Sociology - Naufal Dharmawan Widhiarsa; Wisnu Aji Pangestu; Sumarta Sumarta (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Filial piety to parents is a form of affection, obedience, attention, and respect for the teachings and advice that have been given by them. In this case birrul walidain has a very high position because in Surah Luqman (31): 14, it is commanded that humans must do good to their parents. Islam places parents in a very noble position. Likewise, parents always have the best hopes for their children. This also emphasizes the importance of birrul walidain in the life of a Muslim. The main purpose of this research is to analyze the impact of Birrul Walidain on the sociological perspective between parents and children, as well as its important role in family harmony. Conflicts that are not managed properly will disrupt harmony between parents and children. This research design uses a method that focuses on in-depth understanding related to literature study, which collects and analyzes literature from several primary and supporting sources and academic articles in the field of birrul walidain. The main findings show that there are still children who do not behave properly towards their parents. The implications of this paper show that there are still many children who ignore the way of speaking, and conduct social interactions that are not in accordance with Islamic teachings, causing a bad relationship between parents and children